2009
DOI: 10.1002/jcc.21369
|View full text |Cite
|
Sign up to set email alerts
|

Using electronic polarization from the internal continuum (EPIC) for intermolecular interactions

Abstract: Recently, the vacuum-phase molecular polarizability tensor of various molecules has been accurately modeled (Truchon, J.-F. et al, J Chem Theory and Comput 2008, 4, 1480) with an intra-molecular continuum dielectric model. This preliminary study showed that electronic polarization can be accurately modeled when combined with appropriate dielectric constants and atomic radii. In this article, using the parameters developed to reproduce ab initio Quantum molecular polarizabilities, we extend the application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Numerous computational methods have been developed to determine water location and energetics in binding sites owing to the difficulty of measuring these observables and quantities with experiments. A non-exhaustive list includes: the rolling probe-based Grid software; molecular dynamics probes based methods such as MDMix, 8 MixMD, 9 SILCS; 10 the Monte-Carlo l-dynamics based algorithm JAWS, 11,12 inhomogeneous fluid solvation theory (IFST) based techniques, [13][14][15][16] including the popular method Watermap; 17 implicit and semi-explicit solvent methods such as SZMAP, 18 three dimensional reference interaction site model (3D-RISM), 19 and variational implicit solvent model (VISM). 20 There is growing evidence that judicious use of the above methods is not only useful to further understanding of proteinligand interactions with retrospective studies, but also to assist structure-based medicinal chemistry efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous computational methods have been developed to determine water location and energetics in binding sites owing to the difficulty of measuring these observables and quantities with experiments. A non-exhaustive list includes: the rolling probe-based Grid software; molecular dynamics probes based methods such as MDMix, 8 MixMD, 9 SILCS; 10 the Monte-Carlo l-dynamics based algorithm JAWS, 11,12 inhomogeneous fluid solvation theory (IFST) based techniques, [13][14][15][16] including the popular method Watermap; 17 implicit and semi-explicit solvent methods such as SZMAP, 18 three dimensional reference interaction site model (3D-RISM), 19 and variational implicit solvent model (VISM). 20 There is growing evidence that judicious use of the above methods is not only useful to further understanding of proteinligand interactions with retrospective studies, but also to assist structure-based medicinal chemistry efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Problems of calibrating simulations of ionic solutions are just now being faced in a (fortunately if belatedly) growing literature. Recent contributions include (22,37,47,118,167,(286)(287)(288)(289)(290)(291)(292)(293)(294)(295). As far as I know, no one has attempted to calibrate simulations of seawater or its close relatives, intracellular and Ringer's solutions.…”
Section: Pnpmentioning
confidence: 99%
“…in common usage. Truchon et al have shown that aromatic/charge interactions are dominated by polarization, and can be approximated by an internal continuum model that does not include multipoles per se [59]. …”
Section: Monopole Versus Multipole Electrostaticsmentioning
confidence: 99%